2004
DOI: 10.1038/nature02580
|View full text |Cite
|
Sign up to set email alerts
|

Subtractive proteomic mapping of the endothelial surface in lung and solid tumours for tissue-specific therapy

Abstract: The molecular complexity of tissues and the inaccessibility of most cells within a tissue limit the discovery of key targets for tissue-specific delivery of therapeutic and imaging agents in vivo. Here, we describe a hypothesis-driven, systems biology approach to identifying a small subset of proteins induced at the tissue-blood interface that are inherently accessible to antibodies injected intravenously. We use subcellular fractionation, subtractive proteomics and bioinformatics to identify endothelial cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
395
0
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(403 citation statements)
references
References 38 publications
5
395
0
3
Order By: Relevance
“…These data are supported by our previous findings showing an upregulation of CEACAM1 in endothelial cells after their stimulation by VEGF and the functioning of CEACAM1 as a morphogenetic co-factor for VEGF during capillary formation in vitro, and increased expression in small tumor blood vessels including those of prostate cancer . Additionally, it was shown that CEACAM1 was enriched in tumor endothelial cells compared with whole lung tumor tissue using a subtracting proteomic mapping technique (Oh et al, 2004). Interestingly, our recent data demonstrate that CEACAM1 overexpression in human micro vascular endothelial cells leads to a significant upregulation of VEGF expression among other pro-angiogenic factors such as Ang1, Ang2, angiogenin and IL-8 (Kilic et al, 2005).…”
Section: Discussionmentioning
confidence: 83%
“…These data are supported by our previous findings showing an upregulation of CEACAM1 in endothelial cells after their stimulation by VEGF and the functioning of CEACAM1 as a morphogenetic co-factor for VEGF during capillary formation in vitro, and increased expression in small tumor blood vessels including those of prostate cancer . Additionally, it was shown that CEACAM1 was enriched in tumor endothelial cells compared with whole lung tumor tissue using a subtracting proteomic mapping technique (Oh et al, 2004). Interestingly, our recent data demonstrate that CEACAM1 overexpression in human micro vascular endothelial cells leads to a significant upregulation of VEGF expression among other pro-angiogenic factors such as Ang1, Ang2, angiogenin and IL-8 (Kilic et al, 2005).…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, while there has been a range of studies of individual annexin expression in specific types of primary tumours, there have been no significant previous studies of annexin expression in metastasis. In addition, more recently individual annexins have been proposed as putative tumour biomarkers and potential therapeutic targets in cancer (Oh et al, 2004;Falsey et al, 2006;Wozny et al, 2007). The expression and cellular localisation of annexins have received very little previous study in colorectal cancer, with only annexin A2 having been investigated (Emoto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The overall expression profile of annexins was associated with survival in colorectal cancer, indicating collectively that annexin expression may contribute to outcome and this would be consistent with the putative roles of annexins in some of the cellular processes that led to tumour invasion. These annexins may also represent tumour biomarkers and potential therapeutic targets (Oh et al, 2004;Falsey et al, 2006;Wozny et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We chose the pulmonary vasculature since the lungs contain ~30% of total endothelial surface in the body and, unlike other organs, receive the entire cardiac output of venous blood; hence DDSs targeted to endothelial cells accumulate in lungs [1,3,19,22,39]. In addition, pulmonary endothelium is enriched in some determinant, including thrombomodulin [1,23,[40][41][42][43][44][45]. Previous work showed that anti-TM/GOX targeting to the pulmonary endothelium results in rapid and easily measurable tissue damage due to the production of hydrogen peroxide from the ubiquitous substrates oxygen and glucose [18].…”
Section: Discussionmentioning
confidence: 99%